Aspirin Dose and Treatment Outcomes in Kawasaki Disease: A Historical Control Study in Japan - Ito, Yu; Matsui, Takuya; Abe, Kota; Honda, Takafumi; Yasukawa, Kumi; Takanashi, Jun-ichi; Hamada, Hiromichi (Frontiers in Pediatrics, 2020)
Aspirin has been used as a concomitant drug in the treatment of Kawasaki disease (KD). In recent years, there has been discussion concerning whether high-dose aspirin is appropriate for treatment in the acute phase of KD. We retrospectively investigated the incidence of coronary artery abnormalities (CAAs) and the antipyretic effect of 30 mg/kg/day to 50 mg/kg/day aspirin, the minimum and the maximum approved doses in Japan. This was a single-center, nonrandomized, retrospective, historical cohort study. Patients were routinely treated with 50 mg/kg/day aspirin (50-mg Group) between 2007 and April 2014, and with 30 mg/kg/day aspirin (30-mg Group) between May 2014 and 2016. All patients were given initial and, if necessary, subsequent intravenous immunoglobulin (IVIG) 2.0 g/kg. The primary endpoint was incidence of CAAs defined as a CA diameter with a Z score ≥2.5 at treatment week 4. The secondary endpoint was incidence of further treatment. Incidences were compared using inverse probability weighting analysis adjusting for age, sex, and risk scores. In 587 patients, there was no significant difference in incidence of CAAs (odds ratio in 30-mg Group 0.769, 95% confidence interval (CI): 0.537–1.101, p=0.151). Risk of further treatment after the first IVIG in the 30-mg Group was significantly higher than that in the 50-mg Group (odds ratio 1.379, 95% CI: 1.051–1.811, p=0.021). Although this study has some limitations, the findings suggest that aspirin 50 mg/kg/day may have no significant effect on improving incidence of CAAs compared with 30 mg/kg/day but may have a lower rate of further treatment.